Thermalizing a telescope in Antarctica – analysis of ASTEP observations. Issue 7 (10th September 2015) - Guillot, T.; Abe, L.; Agabi, A.; Rivet, J.‐P.; Daban, J.‐B.; Mékarnia, D.; Aristidi, E.; Schmider, F.‐X.; Crouzet, N.; Gonçalves, I.; Gouvret, C.; Ottogalli, S.; et al.
Abstract The installation and operation of a telescope in Antarctica represent particular challenges, in particular the requirement to operate at extremely cold temperatures, to cope with rapid temperature fluctuations and to prevent frosting. Heating of electronic subsystems is a necessity, but solutions must be found to avoid the turbulence induced by temperature fluctuations on the optical paths. ASTEP 400 is a 40cm Newton telescope installed at the Concordia station, Dome C since 2010 for photometric observations of fields of stars and their exoplanets. While the telescope is designed to spread star light on several pixels to maximize photometric stability, we show that it is nonetheless sensitive to the extreme variations of the seeing at the ground level (between about 0′′.1 and 5′′) and to temperature fluctuations between –30°C and –80 °C. We analyze both day‐time and night‐time observations and obtain the magnitude of the seeing caused by the mirrors, dome and camera. The most important effect arises from the heating of the primary mirror which gives rise to a mirror seeing of 0′′.23 K–1. We propose solutions to mitigate these effects. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)